PELAKSANAAN TRADISI NGEMBLOK DALAM PERKAWINAN (STUDI KASUS DI KECAMATAN SALE KABUPATEN REMBANG) - Ulfa, Kalimatul; Priyanto, At Sugeng; Sumarto, Slamet (Unnes Civic Education Journal, 2015)
Sale Community in Rembang adopts a ngunggahi ngunggah tradition of marriage, in which the woman proposed to or applying for a man who would marry. This tradition is locally called ngemblok. Ngemblok is one form of reverence to the relics of the past, a form of respect for the historical heritage. This tradition was passed on in people’s lives Rembang District especially among Sale community for generations through education in the family.